A review of "Action research for improving educational practice: A step-by-step guide, 2nd edition" - Animaw Tadesse Bayih (College of education, Bahir Dar University, 2023)
Valsa Koshy's book "Action research for improving educational practice: A step-by-step guide, 2nd edition" is a concise guide for teachers and school leaders (hereafter practitioners) seeking to understand the potential of action research as a research methodology for addressing social problems. It also serves as a guide to conducting action research for those interested in solving various practical problems related to their professional practices. While some of the contents may seem similar to previous works in the field, the clarity with which the author wrote the book and the practical examples included throughout the eight chapters makes it profoundly readable. This review attempts to familiarize readers with the main themes, strengths, some salient features, and contributions of the book.